2023
DOI: 10.1097/psy.0000000000001241
|View full text |Cite
|
Sign up to set email alerts
|

Parental Preconception Posttraumatic Stress Symptoms and Maternal Prenatal Inflammation Prospectively Predict Shorter Telomere Length in Children

Gabrielle R. Rinne,
Judith E. Carroll,
Christine M. Guardino
et al.

Abstract: Objective Parental trauma exposure and trauma-related distress can increase risk for adverse health outcomes in offspring, but the pathways implicated in intergenerational transmission are not fully explicated. Accelerated biological aging may be one mechanism underlying less favorable health in trauma-exposed individuals and their offspring. This study examines associations of preconception maternal and paternal posttraumatic stress disorder (PTSD) symptoms with child telomere length, and maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 117 publications
(236 reference statements)
0
2
0
Order By: Relevance
“…Spanning human and nonhuman animal models, other empirical work has found that preconception influences are independent of prenatal factors, suggesting direct effects of preconception factors on offspring outcomes (Class et al, 2013; Guardino et al, 2022; Keenan et al, 2018; Rinne, Carroll, et al, 2023; Swales et al, 2023; Yehuda et al, 2000). For example, experimental manipulation of parental preconception stress among rodents produced altered offspring behavioral and physiological differences characteristic of stress-related disorders (e.g., epigenetic changes; altered stress coping behaviors), independent of pre- and postnatal factors (for reviews, see Chan et al, 2018; Keenan et al, 2018).…”
Section: Preconception and Prenatal Developmental Originsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spanning human and nonhuman animal models, other empirical work has found that preconception influences are independent of prenatal factors, suggesting direct effects of preconception factors on offspring outcomes (Class et al, 2013; Guardino et al, 2022; Keenan et al, 2018; Rinne, Carroll, et al, 2023; Swales et al, 2023; Yehuda et al, 2000). For example, experimental manipulation of parental preconception stress among rodents produced altered offspring behavioral and physiological differences characteristic of stress-related disorders (e.g., epigenetic changes; altered stress coping behaviors), independent of pre- and postnatal factors (for reviews, see Chan et al, 2018; Keenan et al, 2018).…”
Section: Preconception and Prenatal Developmental Originsmentioning
confidence: 99%
“…For example, experimental manipulation of parental preconception stress among rodents produced altered offspring behavioral and physiological differences characteristic of stress-related disorders (e.g., epigenetic changes; altered stress coping behaviors), independent of pre- and postnatal factors (for reviews, see Chan et al, 2018; Keenan et al, 2018). In humans, even with control of prenatal factors, parental preconception stress and parental emotional distress were associated with greater negative emotionality, HPA axis dysregulation, altered neurodevelopment, and shorter telomere length during infancy and childhood (e.g., Guardino et al, 2022; Keenan et al, 2018; Rinne, Carroll, et al, 2023; Swales et al, 2023; Yehuda et al, 2000). Collectively, this multimethod evidence converges around the centrality of preconception influences on offspring outcomes that are distinct from prenatal influences, potentially operating through germline epigenetic mechanisms (Chan et al, 2018; Yehuda & Lehrner, 2018).…”
Section: Preconception and Prenatal Developmental Originsmentioning
confidence: 99%